Fiber optic data communication technological trends and advances - DeCusatis, Casimer (San Diego : Academic Press, 2002)
This book is an authoritative review of current and future trends in the field of telecommunications. Written by industry experts who are developing leading-edge data communication networks, Fiber Optic Data Communication provides professionals and students alike with a look at emerging technologies and their applications. Four of the chapters have been revised from DeCusatis's best-selling book, Handbook of Fiber Optic Data Communications; the remaining eight chapters are all new. Seven helpful appendices, a glossary, and a list of technical acronyms are included. This book can stand alone or as a companion volume to DeCusatis: Handbook of Fiber Optic Data Communication, Second Edition (February 2002, ISBN: 0-12-207891-8). * Includes emerging technologies such as Infiniband, 10 Gigabit Ethernet, and MPLS Optical Switching * Describes leading edge commercial products, including LEAF and MetroCore fibers, dense wavelength multiplexing, and Small Form Factor transceiver packages * Covers all major industry standards, often written by the same people who designed the standards themselves * Includes an expanded listing of references on the World Wide Web, plus hard-to-find references for international, homologation, and type approval requirements * Convenient tables of key optical datacom parameters and glossary with hundreds of definitions and acronyms * Industry buzzwords explained, including SAN, NAS, and MAN networking * Datacom market analysis and future projections from industry leading forecasters.
History of fiber optics / Jeff D. Montgomery -- Market analysis and business planning / Yann Y. Morvan and Ronald C. Lasky -- Small form factor fiber optic connectors / John Fox and Casimer DeCusatis -- Specialty fiber optic cables / Casimer DeCusatis and John Fox -- Optical wavelength division multiplexing for data communication networks / Casimer DeCusatis -- Optical backplanes, board and chip interconnects / Rainer Michalzik -- Parallel computer architectures using fiber optics / David B. Sher and Casimer DeCusatis -- Packaging assembly techniques / Ronald C. Lasky, Adam Singer, and Prashant Chouta -- InfiniBand, the interconnect from backplane to fiber / Ali Ghiasi -- New devices for optoelectronics : smart pixels / Barry L. Shoop, Andre H. Sayles, and Daniel M. Litynski -- Emerging technology for fiber optic data communication / Chung-Sheng Li -- Manufacturing challenges / Eric Maass.
Includes bibliographical references and index.
Keywords: Fiber optics; Data transmission systems; Electronic books